Juliusz Słowacki zilustrowany w 1909 roku - Berkan-Jabłońska, Maria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article presents several examples of illustrations inspired by Słowacki’s poetry which were issued in 1909. They are based on four different methods and styles in the art of illustration. The present author discusses the advantages and disadvantages of these paintings, their artistic value and the public’s reception. The focus is also on the mutual connection between the literary work and its artistic interpretation. The analysis shows the difference between the paintings which created an independent vision of Słowacki’s poetry and the popular art, whose main aim was to popularise the works of this romantic author. The paper also raises the question as to which of these trends have existed most in the culture and have proved to be more popular among readers.